Psychological distress facing the COVID-19 pandemic in dental interns from the Peruvian capital: A cross-sectional study under a multivariable regression model - Cayo-Rojas, César; Córdova-Limaylla, Nancy; Ladera-Castañeda, Marysela; Briceño-Vergel, Gissela; López-Gurreonero, Carlos; Castro-Mena, Manuel; Cornejo-Pinto, Alberto; Agramonte-Rosell, Regina; Cervantes-Ganoza, Luis (Frontiers in Public Health, 2022)
Aim: Psychological distress can be considered a maladaptive response to a stressful situation that occurs when external events or stressors impose demands that cannot be coped with. Therefore, aim of the present study was to assess factors associated with psychological distress in dental interns from Peruvian capital facing COVID-19 pandemic. Materials and Methods: This analytical, observational, cross-sectional study was conducted on 392 Stomatology interns from Peruvian capital during May to July 2022. The validated COVID-19 Peritraumatic Distress Index (CPDI) scale to detect levels of psychological distress consisted of four dimensions: negative mood, changes in behavior and cognitive skills, fatigue and hyperreactivity, and somatization. Pearson's chi-square and Fisher's exact test were used for bivariable analysis. In addition, a logit model was used to assess influence of variables: sex (X1), age group (X2), marital status (X3), monthly economic income (X4), working area in capital city (X5) and living with people vulnerable to COVID-19 (X6), with the psychological distress levels, considering a significance p<0.05. Results: The prevalence of psychological distress in dental interns was severe in 6.4% (95% CI [confidence interval]: 3.9% - 8.8%) and mild in 37.8% (95% CI: 33.0% - 42.6%). According to bivariable analysis, levels of psychological distress by COVID-19 were not significantly associated with sex (p = 0.190), age group (p = 0.418), marital status (p = 0.554), monthly economic income (p = 0.327), working area in capital city (p = 0.993) and living with people vulnerable to COVID-19 (p = 0.134). In addition, according to the logistic regression analysis, none of the variables studied was considered an influential factor (p>0.05) in psychological distress presented by dental interns. Conclusion: The 44.2% of dental interns from the Peruvian capital presented psychological distress facing the COVID-19 pandemic, without any of the possible associated variables of this study significantly affecting this behavioral disorder.